Guidance for market and international marketing skills: a study about the influence on the international performance - Oliveira, Maria Carolina Serpa Fagundes de; Hahn, Ivanete Schneider; Santos, Maríndia Brachak dos; Souza, Gabriela Almeida de; Campos, Daiane Cardozo; Pivetta, Natália Pavanelo (Revista de Administração da UFSM, 2017)
In the face of ongoing social and economic changes and because of the constant search for greater competitiveness, there is currently a need for companies to turn their attention to marketing aspects, in order to seek greater excellence in the generation of value to consumers. This configuration, when allocated to a reality of international trade, can represent the growth of defining and organizational consolidation. Therefore, when observing this ordinance and need, this study aimed to analyze the influence of orientation to the international market and international marketing skills on the international performance of organizations. A collection of data was carried out in conjunction with 53 Brazilian EBTs located in innovation environments. Such data and analyzes using multivariate statistical technique and with the obtained results, it was contacted that the international performance can be influenced by the orientation to the international market.